MENINGKATKAN PEMAHAMAN KELAS VII SMP AMALIA PALU DALAM PEMBELAJARAN PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT PADA PEMBERIAN TUGAS YANG MEMUAT PROBLEM POSING SECARA BERKELOMPOK - Ulfa Rahman (Scolae: Journal of Pedagogy, 2018)
The main problem in this study is the low level of understanding of VII grade students of Amalia Palu in integer addition and subtraction material. Some things that cause these problems, including (1) students still have difficulty in solving problems related to the addition and subtraction operations of integers. (2) understanding the concept of addition operations and the reduction of integers is still lacking, this is because students are less active in learning and only receive information from the teacher without reciprocity from students. To improve students' understanding, the researcher applied a summing learning model and integer reduction on assignments that included problem posing in groups. Problem posing learning model that emphasizes constructivist understanding through group work and is heterogeneous. The results of the research carried out obtained student learning outcomes in the first cycle, of the 20 students who took the final test there were 12 students who completed the study with a percentage of classical completeness of 60 %. Student learning outcomes in the second cycle showed that of the 20 students who took the final test it was seen that 19 students who completed learning or classical learning completeness were 95%. In addition, there is also an increase in student activity in learning activities. Based on these results it can be concluded that addition learning and integer reduction in the assignment of tasks that contain problem posing in groups can improve students' understanding.